PENGEMBANGAN WILAYAH PESISIR KABUPATEN BARRU MELALUI KLASTER PENANGKAPAN IKAN LAUT - Supomo Supomo (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
As the emergence of regional autonomy commenced in the early 2001, the local government is expected not to repeat the central government’s inappropriate management by setting its development priorities. The first priority is to create development system which puts emphasis on the basic economy (people’s basic economy). The second priority is to develop of local leading products from local resources. The third priority is to develop agri-bussiness. The last priority is to establish modern industries based on the local leading products from local resources.In that case the local government of Barru has began to develop the sea fishing catchment cluster. By this cluster model, all of existing stakeholders are involved, until each of them knows their appropriate roles in the system. By developing entrepreneurship, mastering the science and technology, and the empowerment by the local  government, it is expected that the sea  fishing catchment cluster in the sea cluster could grow stronger.